Average heart rate for driver monitoring systems. (2016) - Biondi, F.; Coleman, J.R.; Cooper, J.M.; Strayer, D.L.
With semi-autonomous vehicles being pushed onto the market, driver monitoring systems play a relevant role in determining the user's level of engagement whenever an automated-to-manual transition of control is scheduled to occur. As current monitoring systems heavily rely on steering behaviour and ocular parameters as inputs for their algorithms, this study aims to investigate whether average heart rate represents a sensitive measure of driver mental workload. Participants from three different age groups (21-34, 35-53, 54-70 years old) were considered and the combined effects of mental workload (induced by interacting with the in-vehicle infotainment system via voice) and aging on average heart rate were investigated. Average heart rate was recorded using a portable heart rate monitor for commercial use. Results showed that average heart rate increased as the secondary task became more demanding. Furthermore, a significant task × age interaction suggested that as the secondary task became more demanding, younger drivers showed an increased heart rate compared to older drivers. These results are of the primary importance for the design of adaptive workload monitoring systems.